Causes of Pupils' Failures At Primary Leaving Examinations in Butanda Sub-County Kabale District. - Keinika, Titus (Kabale University, 2024)
The study aimed at investigated the causes of pupils' failure at Primary leaving Examinations Board in Butanda Sub County, Kabale District. It was guided by objectives which were to find out the causes of pupils' failure at Primary Leaving Examinations Board in Butanda Sub County, to assess the level of pupils' academic performance at Primary Leaving Examinations l3oard in Butanda Sub County and to suggest strategies for improving academic performance at Primary Leaving Examinations in Butanda Sub County. The study adopted a cross sectional research design. A sample size of 130 respondents was used. Purposive and simple random sampling techniques were used in selecting respondents. Data collection instruments in this study were questionnaires, interview guides, and documentary reviews. From the findings, it was established that a learning environment with inadequate instructional materials and teaching resources reduced the academic performance of pupils at PLE. Teachers' negative attitude towards work reduced motivation to work which reduced pupils' academic performance in PLE. Limited parental involvement in academic matters of pupils reduced academic performance. Low parent's educational levels reduced academic performance. The study established that pupils' scores were low but there was high performance in social studies compared to other subjects and boys performed better than girls. The study established that making sure teachers are always prepared adequately and have schemes of work, lesson plans, and records of work, ensuring there are regular continuous assessment tests to monitor pupils' progress, visiting teachers in class to supervise teaching, involving teachers to decide on best strategies to improve teaching and learning. The study recommended that the government and other education stakeholders should make concerted efforts to provide adequate instructional materials to primary schools. The government should inject more funds into the educational system for the procurement of teaching and learning facilities and the organizing of in-service training for teachers. Parents should show an active interest in their children's education by providing them with rich instructional materials and also make the home environment conducive to learning by ensuring homework habits, parental support and guidance, and intellectual stimulation.